Morphological Description of the Pancreas in Indian Roller Coracias benghalensis (Linnaeus, 1758) - Haneen Saad Khamas; Intidhar Mohammed Mnati (Wasit Journal for Pure Sciences)
The current study aimed to determine the morphological description of the pancreas in the Indian Roller Coracias benghalensis (Linnaeus, 1758). In this study 15-10 adult live birds were used, which were anesthetized with chloroform and then dissected and the pancreatic gland was removed, then the samples were fixed with fixative solutions. The morphological examination revealed that the Indian roller bird's pancreas is rounded and long, and is a pale pink color. It is found on the lower right side of the body cavity and it has three lobes: the ventral lobe, the dorsal lobe, and the splenic lobe. The ventral lobe was the longest and largest cylindrical lobe and extends within the mesenteric tissue of the duodenal loop. While the dorsal lobe appears flat and lay parallel to the descending arm of the duodenum, the splenic lobe appears in the form of a small volume pear-shaped lobe extending from the center of the dorsal part of the ventral lobe towards the spleen